A Case for Partial Funding of Pensions with an Application to the EU Candidate Countries - Heikki Oksanen (Center for Economic Studies and ifo Institute (CESifo), 2001)
The paper examines the effects of ageing and makes a case for partial pre-funding of pensions. The argument is based on inter-generational fairness in a situation where pension expenditure as compared to wages increases due to low fertility and increasing longevity. We illustrate the approach by using data representing a typical EU Candidate Country of Central and Eastern Europe with a relatively high pension replacement rate. Pre-funding can take place within the public sector or in a privatised second pillar. We emphasise the need for a consistent framework to cover the many different institutional options available for pension financing.
Keywords: 330; Pension system reform; partial pre-funding; ageing